Pengaruh penambahan kolin klorida dalam pakan terhadap produksi, total solid, dan persistensi susu sapi perah laktasi - Diky Trizana; Sri Agus Bambang Santoso; C. Budiarti Soejono (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The study aimed to review the effects of choline chloride addition on milk production, total solid, and persistency in lactating dairy cattle. This experiment was conducted at Wahyu Agung Dairy Farm, Getasan District, Semarang Regency, Central Java. The materials used in this study were 8 lactating dairy cattle. The feed given consisted of napier grass and commercial concentrate (WA Feed) at ratio of 40:60 in dry matter (DM) base at 3.25% BW as basal diet, and mixture of commercial choline chloride (60%) and corncob (40%). The experimental design used a cross-over designs with 2 treatments (T0 and T1) and 4 replications in II periods. The treatments were feed without addition of choline chloride (T0), and the feed with addition of choline chloride at 30 g/head/day (T1). The results showed that there was no effect of choline chloride addition in feed on dry matter intake, being 13.29 and 14.12 kg/head/day for T0 and T1, respectively. However, milk production was significantly different (P<0.05) between T0 and T1, being 13.48 and 13.91 l/head/day, as well as in total solid (T0= 12.61% vs T1 = 13.12%; P<0.05), eventhough there were no significant in persistency of milk (T0 = 4.17% vs T1 = 2.83%; p>0.05). The conclusions of this experiment was addition of choline chloride in feed as much as 30 g/head/day could increase milk production and total solid, but did not affect the persistency milk production. Keywords: Choline chloride, milk production, total solid, persistency